2019
DOI: 10.1007/s40261-019-00756-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Loxoprofen Hydrogel Transdermal Patch Versus Loxoprofen Tablet in Chinese Patients with Myalgia: A Double-Blind, Double-Dummy, Parallel-Group, Randomized, Controlled, Non-Inferiority Trial

Abstract: Background and Objective Loxoprofen (LOX) is a nonsteroidal anti-inflammatory drug (NSAID). Although oral administration of LOX has been widely prescribed, clinical guidelines for osteoarthritis generally recommend topical rather than oral NSAIDs in specific patients. However, there is limited information on the effects of loxoprofen sodium oral (LOX-O) versus loxoprofen sodium hydrogel transdermal patch (LOX-T) in myalgia patients. Hence, this non-inferiority study was designed to compare the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…Topical Treatment. Zhao et al [36] found that oral loxoprofen sodium (LOX-O) was found to be comparable to loxoprofen sodium hydrogel transdermal patch (LOX-T), indicating promising topical use of nonsteroid anti-inflammatory drugs (NSAIDS). Coskun Benlidayi et al [37] found that both ibuprofen gels and creams had significant clinical efficacy.…”
Section: Drug Treatmentsmentioning
confidence: 99%
“…Topical Treatment. Zhao et al [36] found that oral loxoprofen sodium (LOX-O) was found to be comparable to loxoprofen sodium hydrogel transdermal patch (LOX-T), indicating promising topical use of nonsteroid anti-inflammatory drugs (NSAIDS). Coskun Benlidayi et al [37] found that both ibuprofen gels and creams had significant clinical efficacy.…”
Section: Drug Treatmentsmentioning
confidence: 99%
“…Loxoprofen sodium is the first non-steroidal antiinflammatory drug (NSAID), which belongs to the propionic acid group which includes commonly used drugs ibuprofen and naproxen. 13,14 The main therapeutic mechanism of loxoprofen sodium is its inhibition on the synthesis of prostaglandin, and its analgesic effect is approximately 10-20 fold of several other NSAIDs such as indomethacin, ketoprofen, or naproxen. 15 Recognized as a promising analgesic, antiinflammatory and antipyretic effects have been observed on the clinical trials on loxoprofen sodium.…”
Section: Introductionmentioning
confidence: 99%
“…Omega-3 fatty acids are long-chain polyunsaturated fatty acids composed of a mixture of α-linolenic (ALA, 18:3 n-3), eicosapentaenoic (EPA, 20:5 n-3), and docosahexaenoic (DHA, 22:6 n-3) acids. Vegetable oils, such as olive and flaxseed oil, are rich in ALA while, marine oils are major sources of EPA and DHA (Zhao et al., 2019 ). Since the human body is unable to synthesize omega-3 fatty acids, which are important to our diet, they must be supplied from external sources (Lavie et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%